Participatory determinants of innovation and their impact on plantain production systems in Cameroon - (:unkn) unknown (My University, 2006)
Current statistics question the capacity of food-crop production to meet the challenges of food security in Central Africa. However, for local food crops like plantain, the potential for improving productivity is very high. In response to this challenge, after identification of the most serious constraints, an interdisciplinary team used participatory research and action-research tools to try and speed up the adoption of technical innovation by farmers. The project began in 1990 in South-West Province and subsequently expanded to include 100 plantain producers and 60 extension technicians in the Central and Southern Provinces of Cameroon. The approach used produced satisfactory results as far as the adoption and dissemination of methods of multiplication and cleaning of planting material were concerned but there was resistance to new cropping practices involving intercrops and crop rotation. The project resulted in major technical changes in plantain production systems in Cameroon that not only increased productivity and food security but also reduced deforestation showing that sustainable intensification is possible in sub-Saharan Africa.
Keywords: African Research